1950
DOI: 10.1177/004051755002000405
|View full text |Cite
|
Sign up to set email alerts
|

Law of Critical Yarn Diameter and Twist Influence on Yarn Characteristics

Abstract: The effect of increased twist upon yarn density is explored and a law of critical diameter is postulated. It is suggested that at the time at which a yarn breaks under tensile load the density of the yarn is equal to the fiber density. The influence of twist on contraction is examined and prediction formulas are given for cotton, woolen, worsted, and rayon yarns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

1963
1963
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 0 publications
1
16
0
1
Order By: Relevance
“…They showed that a normal 100% wool worsted hosiery )''lrn lost 20% of its specific volume, while a hi-bulk acrylic yarn was reduced by only 15%. Barella [1] JrOdt1ced further evidence to support this point and s lOwed that filament rayon, spun rayon, and wooleñ~d WOrsted yarns lost 10-20% of their untensioued r.tameter when subjected to a load of 75 g. It was…”
Section: Y Arll Propertiesmentioning
confidence: 85%
“…They showed that a normal 100% wool worsted hosiery )''lrn lost 20% of its specific volume, while a hi-bulk acrylic yarn was reduced by only 15%. Barella [1] JrOdt1ced further evidence to support this point and s lOwed that filament rayon, spun rayon, and wooleñ~d WOrsted yarns lost 10-20% of their untensioued r.tameter when subjected to a load of 75 g. It was…”
Section: Y Arll Propertiesmentioning
confidence: 85%
“…Using the 10 measured values of 8 and d, average values were obtained by taking the arithmetic mean of 8 and the root mean square value of d. The RMS value was chosen because d' appears in Equation 1.…”
Section: Calculation Of Valuesmentioning
confidence: 99%
“…The relationships between physical properties and both the tensile property and geometry of the cross-section of a yarn have been widely investigated [11][12][13][14][15][16][17][18]27]. Barella [19] measured the yarn diameter under different tensile loads using a projection microscope. Carvalho et al [20] measured the yarn diameter employing coherent optical signal processing.…”
Section: Introductionmentioning
confidence: 99%